Исследование параметрической оптимизации массы двухступенчатого планетарного механизма типа A̅I̅ - II - Матусевич, Владимир Анатольевич; Шарабан, Юрий Владимирович; Шехов, Александр Владимирович; Абрамов, Владимир Тимофеевич (НТУ "ХПИ", 2018)
Рассмотрена методика построения целевой функции массы двухступенчатого планетарного механизма типа A̅I̅ - II с учетом условий прочности зубчатых зацеплений и областей существования планетарных ступеней механизма. Предложен подход для исследования экстремальных свойств целевой функции массы планетарного механизма. На основе экстремальных свойств целевой функции построена математическая модель оптимизации массы планетарного механизма. В качестве параметров оптимизации приняты значения передаточных отношений, числа сателлитов, коэффициентов приведения масс, отношения диаметров сателлитов и параметры прочности зубчатых зацеплений ступеней планетарного механизма. Приведен пример оптимального проектирования конструкции минимальной массы планетарного механизма типа A̅I̅ - II.

Methodology of construction of objective function of mass of two-stage planetary mechanism of type A̅I̅ - II is considered taking into account the terms of durability of the toothed hooking and areas of existence of the planetary stages of mechanism. Offered approach for analysis of extreme properties objective function of mass of planetary mechanism. On the basis of extreme properties of objective function the mathematical model of optimization of mass of planetary mechanism is built. As parameters of optimization taken on values of transmission relations, number of satellites, coefficients of bringing the masses over, relations of diameters of satellites and parameters of durability of the toothed hooking of the stages of planetary mechanism. The features of extreme properties of objective functions of mass of the second stage of planetary mechanism are shown by corresponding charts. Given to recommendation on the choice of values of parameters of optimization. An example of the optimal design of construction of minimum mass of planetary mechanism of type A̅I̅ - II is made.
Analysis of mass parameter optimization two stage planetary mechanism of type A̅I̅ - II
Keywords: функция целевая; минимизация массы; прочность; objective function; minimization of mass; durability